Management of polycystic ovary syndrome among Indian women using myo‐inositol and D-chiro-inositol - Vyas, Lila (Bioinformation, 2022)
Myo-Inositol and D-chiro-inositol (MI-DCI) are used in the treatment of polycystic ovarian syndrome (PCOS) due to their insulin-sensitizing actions. Therefore, it is of interest to evaluate the treatment patterns, clinical effectiveness and safety of MI-DCI combination in management of PCOS in Indian women .Data from 50 healthcare centers across India between September 2019 and February 2020 were used in the study. Women aged 12-45 years diagnosed with PCOS, who had received MI-DCI (550-150 mg) were included. The outcome parameters were change in weight, luteinizing hormone (LH)/follicle stimulating hormone (FSH) ratio, hirsutism, blood glucose and insulin levels, HOMA-IR, and lipid profile. 283 women (mean age: 27.74 years; body mass index: 26.89 kg/m2); of which 197 (69.61%) reported reduction in weight after treatment with MI-DCI. The proportion of hirsutism score reduced after treatment, no hirsutism increased from 31.07% to 50.51% and the severe reduced from 4.85% to zero and moderate from 32.52% to 6.12%. There was a significant reduction in LH:FSH ratio (mean difference: 0.25 mg/dL; p=0.021), free testosterone (mean difference: 1.49; p<0.001) and dehydroepiandrosterone (mean difference: 21.49; P<0.001) levels after regular use of MI-DCI tablets.Treatment with MI-DCI resulted in significant improvement in insulin, HOMA score, FPG, PPG and lipid profile. The therapy restored menstruation and spontaneous ovulation and significantly attenuated the LH/FSH ratio. Thus, MI-DCI (550-150 mg) has shown multidimensional benefits in improving the hormonal, glycemic, and lipid profile of women with PCOS with considerable efficacy and tolerability.